The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.23085
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group protein A2 overexpression indicates poor prognosis for cancer patients: a meta-analysis

Abstract: Overexpression of the high mobility group protein A2 (HMGA2), an architectural transcription factor, has been linked to poor prognosis in many malignancies, although this remains controversial. Herein, we conducted a meta-analysis to investigate whether HMGA2 has prognostic value, and evaluated the association between HMGA2 and clinicopathologic factors in malignancies. A total of 29 studies involving 4114 patients were included in this meta-analysis. The pooled results demonstrated that elevated HMGA2 predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…10 An overexpression of HMGA2 was attributed to oncogenic traits and described in malignancies of different entities. [11][12][13][14][15][16][17][18][19][20] Expression of HMGA2 in breast cancer has been discussed as a prognostic or even predictive biomarker upon expression in primary tumors or circulating tumor cells. [20][21][22][23] Until very recently, physiologic and oncogenic properties of HMGA2 proteins were mainly linked to functions of HMGA2 in the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…10 An overexpression of HMGA2 was attributed to oncogenic traits and described in malignancies of different entities. [11][12][13][14][15][16][17][18][19][20] Expression of HMGA2 in breast cancer has been discussed as a prognostic or even predictive biomarker upon expression in primary tumors or circulating tumor cells. [20][21][22][23] Until very recently, physiologic and oncogenic properties of HMGA2 proteins were mainly linked to functions of HMGA2 in the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggested that HMGA2 expression did not predict patients’ prognosis (overall and disease-free survivals) based on TCGA datasets (esophagus, stomach, colon, and rectum cancers). However, it remains controversial because negative prognostic impacts of HMGA2 overexpression in the above cancer types have been reported previously [54,55,56,57,58,59]. We hypothesized that such discrepancy may be resulted from the source of cancer patients’ data, which can be supported by a recent meta-analysis based on literatures (15 cancer types) and TCGA datasets (33 cancer types) [60].…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, HMGA2 is re-expressed and becomes again highly elevated in benign (Dreux et al 2010 ; Tallini et al 2000 ) as well as malignant neoplasms such as ovarian cancer (Wu and Wei 2013 ; Xi et al 2014 ; Jin et al 2018 ), breast cancer (Wu et al 2016 ; Sgarra et al 2018 ), lung cancer (Kumar et al 2014 ), gastrointestinal cancer (Mito et al 2017 ; Zhu et al 2017 ; Huang et al 2018 ; Wang et al 2011 ; Zhang et al 2016 ), and pancreatic cancer (Strell et al 2017 ; Piscuoglio et al 2012 ). Importantly, diverse meta-analyses revealed a correlation of high HMGA2 expression with poor patient’s survival in various malignancies such as gastric, colorectal as well as head-and-neck cancers (Binabaj et al 2019 ; Nie et al 2018 ; Huang et al 2018 ). For hepatobiliary cancers, in particular HCC, cholangiocarcinoma and gallbladder cancer (Binabaj et al 2019 ; Nie et al 2018 ; Huang et al 2018 ) as well as PDAC (Huang et al 2018 ; Binabaj et al 2019 ), poor survival was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, diverse meta-analyses revealed a correlation of high HMGA2 expression with poor patient’s survival in various malignancies such as gastric, colorectal as well as head-and-neck cancers (Binabaj et al 2019 ; Nie et al 2018 ; Huang et al 2018 ). For hepatobiliary cancers, in particular HCC, cholangiocarcinoma and gallbladder cancer (Binabaj et al 2019 ; Nie et al 2018 ; Huang et al 2018 ) as well as PDAC (Huang et al 2018 ; Binabaj et al 2019 ), poor survival was reported. Of note, not all tumors with elevated HMGA2 expression show significant association with survival rates (e.g., ovarian cancer Huang et al 2018 ; Nie et al 2018 ) or esophageal cancer (Huang et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%